Fructose and lactose intolerance and malabsorption testing: the relationship with symptoms in functional gastrointestinal disorders. Issue 11 (9th April 2013) - Wilder‐Smith, C. H.; Materna, A.; Wermelinger, C.; Schuler, J.
Summary Background The association of fructose and lactose intolerance and malabsorption with the symptoms of different functional gastrointestinal disorders (FGID) remains unclear. Aim To investigate the prevalence of fructose and lactose intolerance (symptom induction) and malabsorption and their association with clinical gastrointestinal (GI) as well as non‐GI symptoms in FGID and the outcome of dietary intervention. Methods Fructose and lactose intolerance (defined by positive symptom index) and malabsorption (defined by increased hydrogen/methane) were determined in 1372 FGID patients in a single centre using breath testing. Results were correlated with clinical symptoms in different FGID Rome III subgroups. The effectiveness of a targeted saccharide‐reduced diet was assessed after 6–8 weeks. Results Intolerance prevalence across all FGIDs was 60% to fructose, 51% to lactose and 33% to both. Malabsorption occurred in 45%, 32% and 16% respectively. There were no differences in intolerance or malabsorption prevalence between FGID subgroups. FGID symptoms correlated with symptoms evoked during testing (r = 0.35–0.61. P < 0.0001), but not with malabsorption. Non‐GI symptoms occurred more commonly in patients with intolerances. Methane breath levels were not associated with constipation using several cut‐off thresholds. Adequate symptom relief was achieved in >80% of intolerant patients, irrespective of malabsorption. Conclusions Fructose and lactose intolerances are common in FGID and associated with increased non‐GI symptoms, but not with specific FGID subtypes. Symptoms experienced during breath testing, but not malabsorption, correlate with FGID symptoms. Effective symptom relief with dietary adaptation is not associated with malabsorption. Mechanisms relating to the generation of GI and non‐GI symptoms due to lactose and fructose in FGID need to be explored further.